High-intensity interval training improves respiratory and cardiovascular adjustments before and after initiation of exercise - Ito, Go; Feeley, Marina; Sawai, Toru; Nakata, Hideomi; Otsuki, Shingo; Nakahara, Hidehiro; Miyamoto, Tadayoshi (Frontiers in Physiology, 2024)
Purpose: High-intensity interval training (HIIT) may induce training-specific physiological adaptations such as improved respiratory and cardiovascular adjustments before and after the onset of high-intensity exercise, leading to improved exercise performance during highintensity exercise. The present study investigated the effects of HIIT on time-dependent cardiorespiratory adjustment during maximal exercise and before and after initiation of highintensity exercise, as well as on maximal exercise performance. Methods: 21 healthy male college students were randomly assigned to HIIT group (n=11) or control group (n=10). HIIT group performed training on a cycle ergometer once a week for 8 weeks. The training consisted of three bouts of exercise at 95% maximal work rate (WRmax) until exhaustion.Before and after the HIIT program, dynamic cardiorespiratory function was investigated by ramp and step exercise tests, and HIIT-induced cardiac morphological changes were assessed using echocardiography. Results: HIIT significantly improved not only maximal oxygen uptake and minute ventilation, but also maximal heart rate (HR), systolic blood pressure (SBP), and time to exhaustion in both exercise tests (P < 0.05). Time-dependent increases in minute ventilation (VE) and HR before and at the start of exercise were significantly enhanced after HIIT. During high-intensity exercise, there was a strong correlation between percent change (from before to after HIIT program) in time to exhaustion and percent change in HRmax (r=0.932, P< 0.001). Furthermore, HIIT-induced cardiac morphological changes such as ventricular wall hypertrophy was observed (p<0.001). Conclusion: We have demonstrated that HIIT at 95% WRmax induces training-specific adaptations such as improved cardiorespiratory adjustments, not only during maximal exercise but also before and after the onset of high-intensity exercise, improvement of exercise performance mainly associated with circulatory systems.